(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This essay revisits the teachings of Tadashi Endo and the practices of Butoh-Ma, proposing the notion of pedagogies of impermanence. It articulates critical reflection with a testimonial character, bringing dance and transmission closer to an ethics of sustaining the fall. In dialogue with Aby Warburg (2020) and Didi-Huberman (2018, 2019, 2020, 2021), it understands dance as an unarchiving operation, capable of raising new survivals through bodily memory, presence, and the sensitive sharing of knowledge. Rather than preserving stable forms, pedagogies of impermanence allow presences, gestures and images to continue operating beyond death and disappearance.